UPAYA PENGUSAHA MUDA MERAIH KEBERHASILAN BERWIRAUSAHA DALAM BISNIS JAS FORMAL “PROPAGET” MELALUI USAHA E-COMMERSE - Nurpatimah, Aam; Solihah, Zahira Auladina; Sianturi, Risbon (Universitas Sahid, 2023)
The movement of technological advancements, especially in social media, is very tied to today's life. Social media has very helpful uses in various aspects of life, one of which is in the field of entrepreneurship. From this, it is necessary to understand how important the use of social media is to the chances of success of a business. The research method used is the descriptive method. In addition, in obtaining data using interview techniques with Propaget business owners as the subject studied. The research findings found that efforts to achieve the success of Propaget's business in its management, where Propaget's business has 2 admins and 2 employees for promotion on social media by displaying video content and doing live broadcasts on social media such as Shopee and tik-tok shop as a marketing strategy. Currently, the production of suits, pants and vests, robes, ordinary cocoa, and children's cocoa can reach 200 pcs a day. Thus, Propaget's formal suit business can achieve success in making profits in entrepreneurship through social media.